Aircraft wing flutter control - Tavalla, Sahar Sadat (2013)
This research includes the design of a multivariable control system for aircraft wings. Two objectives are desired. The first is to control the vibrational problem for low-speed flight by applying a feedback control strategy. The second goal is to demonstrate that the controller for this wing assembly dissipates the least energy by comparing an alternative controller design technique. Simple procedures using established methods relating the wing vibrational problems, are outlined. The control strategies invoked using a simplified flutter dynamic model. A compensator designed to provide enhanced flutter suppression was employed. The transient performance of the system was computed for various flight velocities. Comparison of the energy dissipation for the gain ratios investigated was obtained. Numerical simulation was used to demonstrate the effectiveness of the approach advocated.